Oral esomeprazole in Japanese pediatric patients with gastric acid‐related disease: Safety, efficacy, and pharmacokinetics. Issue 1 (8th February 2019) - Shimizu, Toshiaki; Nakayama, Yoshiko; Ishii, Eizaburo; Ida, Shinobu; Satou, Tomoki; Tokuhara, Daisuke; Arai, Katsuhiro; Nii, Masahiro; Rydholm, Hans; Yajima, Toshitaka; ,
Abstract: Background: Proton pump inhibitors (PPI) are widely used for the treatment of gastric acid‐related disease, but they are not approved for use in children in Japan. To assess the safety, pharmacokinetics, pharmacodynamics, and efficacy (gastrointestinal symptom improvement) of PPI in Japanese pediatric patients with gastric acid‐related disease, we conducted an 8 week, open‐label, parallel‐group, multicenter, phase I/III study of once‐daily oral esomeprazole use. Methods: Japanese children, aged 1–14 years with gastric acid‐related disease, were stratified by weight and age into five groups (10 patients/group) to receive esomeprazole as granules for suspension (10 mg) or capsules (10 mg or 20 mg) once daily. Results: Esomeprazole was absorbed and eliminated rapidly in all groups, with a median time to reach maximum plasma concentration of 1.47–1.75 h, an arithmetic mean terminal elimination half‐life of 0.80–1.37 h, and a weight‐correlated apparent total body clearance of 0.216–0.343 L/h/kg. Area under the plasma concentration–time curve during a dosage interval and maximum plasma drug concentration were generally higher in groups given a higher dose (20 mg) or with a lower age/weight, but also in patients identified as poor metabolizers on cytochrome P450 2C19 genotype. Most patients who had any upper gastrointestinal symptoms at baseline were asymptomatic at the end of the study. Thirty‐three patients (66%) reported ≥1 adverse events, including three patients who reported serious adverse events not judged to be causally related to esomeprazole. Conclusions: Oral esomeprazole, at 10 mg or 20 mg once daily, had a similar safety, efficacy, and pharmacokinetic profile in Japanese pediatric patients to that previously seen in adults and Caucasian children.